Tuberculosis in goats in Benoue area of North Cameroon: Prevalence, diagnostic performance of intradermal tuberculin skin test and zoonotic risk factors - Julius Awah-Ndukum; Emmanuel Assana; Victor Ngu-Ngwa; Achille Olivier Tchedele; Mohamed Moctar Mouliom Mouiche; Jean-Pierre Kilekoung Mingoas; André Pagnah Zoli (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Tuberculosis (TB) due to Mycobacterium bovis is a wasting disease of animals with severe public health significance. Though widely diagnosed in cattle and the performance of Tuberculin Skin Test (TST) at different cut-off points compared in various environmental conditions, there is dearth of information with respect to TB in goats in Cameroon. This study estimated the prevalence of bovine TB in goats in Benuoe area of Cameroon, based on the performance of TST against detection of tuberculous-like lesions and acid-fast bacilli as gold tests. The study detected goat TB based on tuberculous-like lesions (27.87%), acid-fast bacilli (3.29%); and bovine TB positive reactions (12.28%, 95%CI: 9.19-15.95), (8.95%, 95%CI: 6.31-12.23) and (5.37%, 95%CI: 3.36-8.09) at Single intradermal cervical tuberculin (SICT) ≥2.5mm, ≥3mm, and ≥4mm and (2.30%, 95%CI: 1.06-4.32), (1.79%, 95%CI: 0.72-3.65) and (1.02%, 95%CI: 0.28- 2.60) at Single intradermal comparative cervical tuberculin (SICCT) ≥2mm, ≥3mm, and ≥4mm cut-off points, respectively. SICT and SICCT sensitivity (11.76%) against detection of tuberculous-like lesions was significantly lower [p<0.05] with slight agreements [Kappa=0.161] compared to sensitivity (100%) and perfect agreements [Kappa=1.00] against detection of acid-fast bacilli at these cut-offs. The Bayesian model revealed a goat TB prevalence of 18.41% (95%CI: 11.73-27.00) using SICT and 4.28 (95%CI: 1.26-8.60) using SICCT with the performance characteristic being higher for SICT than SICCT at ≥2mm cut-off. However, two-graph ROC (TG-ROC) analysis revealed that the optimal goat TB diagnosis with SICCT was at ≥2mm cut-off point. Many goat handlers were aware of health hazards of zoonotic TB but ignorant about goat TB and its possible zoonotic transmission to humans. The study reports the first comparative tuberculin skin test of goats in Benoue area of North-Cameroon and confirmed that zoonotic TB is a neglected health and production problem of goats in Cameroon that needs further investigated.